2015
DOI: 10.1007/s11274-015-1969-0
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial effects of quaternary bis-phosphonium and ammonium salts of pyridoxine on Staphylococcus aureus cells: A single base hitting two distinct targets?

Abstract: We studied the effects of quaternary bis-phosphonium and bis-ammonium salts of pyridoxine with lipophilic substituents on the survival and morphology of Staphylococcus aureus cells. We found that, while originating from the same base, they exhibit considerably different antimicrobial mechanisms. In the presence of Ca(2+) ions the MIC and MBC values of ammonium salt increased 100-fold, suggesting that Ca(2+) ions can successfully impede the membrane Ca(2+) ions exchange required for ammonium salt incorporation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 16 publications
1
14
0
1
Order By: Relevance
“…Therefore, it can be suggested that the cell wall damage associated with the removal of Ca 2+ ions is one of the possible mechanisms of their antibacterial activity. Similar observations have been reported in our recent paper [53] for a series of quaternary bis-phosphonium salts of pyridine derivatives, which exhibited broad-spectrum antibacterial activity against Grampositive pathogens including methicillin-resistant strains of S. aureus.…”
Section: Antibacterial Activitysupporting
confidence: 90%
“…Therefore, it can be suggested that the cell wall damage associated with the removal of Ca 2+ ions is one of the possible mechanisms of their antibacterial activity. Similar observations have been reported in our recent paper [53] for a series of quaternary bis-phosphonium salts of pyridine derivatives, which exhibited broad-spectrum antibacterial activity against Grampositive pathogens including methicillin-resistant strains of S. aureus.…”
Section: Antibacterial Activitysupporting
confidence: 90%
“…33 Synthesis of TPP + -TAMRA conjugates (42 and 43) is shown in Figure 6A. Potassium phthalimide (35) was stirred with excess 1,10-dibromodecane (34) to give 10-bromodecylphthalimide (36). Column chromatography was used to remove the unreacted dibromoalkane.…”
Section: ■ Resultsmentioning
confidence: 99%
“… Several toxic pathways. [ 331 ] [ 332 ] Composite-Based Nanomaterials Ceramic Matrix Nano-composites 1–100 S. aureus E. coli High antimicrobial effect Inhibit the bacterial growth Physical interaction Particle size Heat pressure [ 333 ] Metal Matrix Nano-composites 1–100 A. baumannii S. aureus E. coli K. pneumonia Inhibit the bacterial growth Physical interaction formation of irregular pores in the outer membrane of bacteria Particle size Depends on the content in the medium [ 334 ] Polymer Matrix Nano-composites 1–100 A. baumannii S. aureus E. coli K. pneumonia MDR Inhibit the bacterial growth Physical interaction Depends on the content in the medium [ 335 ] …”
Section: Nanomaterialsmentioning
confidence: 99%